Application of remote sensing technologies for estimating sugarcane yield - Zenteno Cruz, Guillermo Alberto; Palacios Vélez, Enrique; Tijerina Chávez, Leonardo; Flores Magdaleno, Héctor (Revista Mexicana de Ciencias Agrícolas, 2017)
The sugarcane producers are constantly looking to reduce costs, increase productivity and yield. On the other hand, the prediction of the yield of the crops for a better planning of agricultural policies and food security in a globalized market economy is very important. The present investigation was carried out in the area of supply of Sugarmill Emiliano Zapata, in the state of Morelos, in an area of 10 664 ha, during the agricultural cycle 2009-2010. The objective of the study was to calibrate a methodology to estimate the yield of sugarcane ( Saccharum officinarum ) based on the temporal analysis of vegetation indices of normalized diff erences (NDVI) and moisture stress indexes (MSI) obtained from Landsat- 7 ETM+ and crop evapotranspiration (ETc) estimated by calculating the variable Kc as a function of NDVI indexes and using reference evapotranspiration (ETo) obtained from meteorological stations. As a result of the study, relationships between the average values of the indices and the ETc were obtained, with the yield measured in the field in 23 control plots; with an R2 being 0.92, 0.77 and 0.85, respectively. From the best fit model, we estimated the average yield for the study area of 114.3 t ha-1 . The Secretariat of Agriculture Fisheries and Food; through the Agro-Food and Fisheries Information Service (SIAP), reported an average yield in Morelos for the year 2009 of 115.4 t ha-1 . This allows to know the effectiveness of the estimates made.